Anti-inflammatory activity of Curcuma wanenlueanga Saensouk, Thomudtha & Boonma rhizomes and the search for its bioactive markers by harmonizing bioassay-guided isolation and network pharmacology - Wisuwat Thongphichai; Hasriadi Hasriadi; Peththa Wadu Dasuni Wasana; Sanith Sri Jayashan; Boonchoo Sritularak; Pasarapa Towiwat; Suchada Sukrong (BMC Complementary Medicine and Therapies)
Abstract Background Rhizomes of Curcuma wanenlueanga Saensouk, Thomudtha & Boonma have been used in Thai traditional medicine and are included as an ingredient in a Thai traditional liniment formula listed by the Ministry of Public Health of Thailand for treating symptoms related to joints and muscle inflammation. However, anti-inflammatory activity and bioactive constituents of C. wanenlueanga have not yet been investigated. Thus, this study aimed to investigate the anti-inflammatory activity and underlying mechanism of C. wanenlueanga rhizome extract and its responsible bioactive components. Methods The fractionation of bioactive compounds from C. wanenlueanga extract was guided by antioxidant activity on DPPH and Griess assays, and anti-inflammatory activity on LPS-induced RAW 264.7 cells. The biological activities of isolated compounds were first predicted by network pharmacology and further confirmed in cell-based assay with LPS-induced RAW 264.7 cells and enzyme-linked immunosorbent assay (ELISA) of tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). Results The ethanolic extract of C. wanenlueanga rhizomes was proved to show anti-inflammatory activity on LPS-induced RAW 264.7 cells. Three curcuminoids including curcumin (1), demethoxycurcumin (2), dihydrodemethoxycurcumin (3), and two sesquiterpenoids, namely curcumenone (4), and zedoarondiol (5) were separated from anti-inflammatory fractions of C. wanenlueanga extract. The anti-inflammatory activity of these compounds to attenuate the productions of TNF-α and IL-6 was predicted by pharmacological network. The inflammatory assays, including the Griess assay for NO and ELISA for TNF-α and IL-6, confirmed that all isolated compounds reduced the production of these inflammatory mediators. Conclusion The present study shows the accordance between the results from pharmacological network and cell-based assays, which indicate the anti-inflammatory activity of C. wanenlueanga rhizomes and their bioactive constituents. This suggests the potential of bioactive compounds 1–5 to be used for quality assessment of C. wanenlueanga extract in the development of herbal products.